The effect of superovulation treatments on sperm transport, reproductive parameters, and plasma hormone levels in ewes - Tufts, M. A.(Mark Andrew) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.